KOMUNIKASI POLITIK DALAM PENGEMBANGAN EKONOMI KREATIF DEMI MEWUJUDKAN SGDS PEKERJAAN YANG LAYAK DAN PERTUMBUHAN EKONOMI - Firliandoko, Robby; Sarwoprasodjo, Sarwititi; Wahyudin, Cecep; Amalia, Nadia (JURNAL SIGNAL, 2024)
Creative Economy (Ekraf) is an economic sector that is believed to be the backbone of the nation in the future. Its nature which prioritizes ideas and human resources is a factor in why creative economy is believed to be a source of Indonesia's economy in the future. Advancing the creative economy does not only require plans and desires but also policies from the Government. In this practice, Political Communication plays a role in advancing and developing the creative economy for the realization of the 8th SDGs, namely Decent Work and Economic Growth. Through qualitative research by conducting direct observations, reading documents timeline of the journey of the Creative Economy Forum and the Bogor Regency Creative Economy Committee and analyzing the news presented in the media, this research found that the practice of Political Communication in development occurred starting from community movements who were creative economic actors, then creating collective action by forming forums. and convey aspirations directly to the Regent as Regional Head with the support of reporting provided by the Media. This practice was successful in encouraging Bogor Regency to publish political products by issuing Bogor Regent Regulation Number 38 of 2021 concerning Creative Economy Development.